Exploring Halal Destination Loyalty Through Halal Destination Attributes, Halal Memorable Tourism Experiences, and Economic Impact in Muslim-Friendly Nature Tourism in West Java - Putra, Wira Pramana; Sari, Diana; Komala dewi, Rita; Sumengkar, Apung; Nidar, Sulaeman Rahman (Yayasan Riset dan Pengembangan Intelektual, 2024)
This study investigates the role of Halal Destination Attributes (HDA) and Halal Memorable Tourism Experiences (HMTE) in influencing Halal Destination Loyalty (HDL) within Muslim-friendly nature-based tourism in West Java. The research focuses on exploring the interplay between these factors in shaping loyalty among visitors to the top three Muslim-friendly nature destinations in West Java: Kawah Putih in Bandung Regency, Pantai Balongan Indah in Indramayu Regency, and Sari Ater Hot Spring Resort in Subang Regency. The study employed a quantitative research design. Data were collected using a nonprobability purposive sampling method, targeting individuals who had visited one of the selected destinations at least twice, with their most recent visit occurring within the last 12 months. Using G*Power for sample size calculation, the survey garnered 143 valid responses from an initial target of 107 respondents. Data analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS software. The results demonstrate that both Halal Destination Attributes and Halal Memorable Tourism Experiences positively and significantly influence Halal Destination Loyalty. Additionally, Halal Destination Attributes are shown to have a significant positive effect on Halal Memorable Tourism Experiences. These findings underscore the importance of enhancing both destination attributes and memorable experiences to foster loyalty among Muslim-friendly nature-based tourism visitors